Charging of a rodlike grain in plasma flow - R.I. Golyatina; S.A. Maiorov (Physical Sciences and Technology, 2018)
In present work on the basis of numerical modeling by the dynamics of many particles, a self-consistent problem of the formation of a charge accumulated by a dusty particle of a rodlike shape in a twotemperature plasma flow is considered. An analytical model useful for understanding the phenomenon of ion focusing and its effect on the formation of the surface charge of a needle was considered. Pairwise radial correlation functions evaluated in the approximation of binary interaction for moving particles with a stationary Coulomb center. Using conservation law for the momentum ion velocity component has been determined. It was noticed that electron shielding does not influence on the ion focusing density peak value. In that reason ion focusing parameters in the concrete doesn’t depend on the electron screening Debye radius. A system with Coulomb particles containing moving point particles, ions and electrons, and fixed spheres have been chosen. The cases of dielectric and metallic dust grains having different orientations with respect to the flow direction are considered.